Shift-learning towards remote area on freshers of english education at Universitas Ahmad Dahlan - Muhammad Sandy Al Fath; Muhammad Abdul Azis; Didik Murwantono (Universitas Muhammadiyah Malang, 2020)
The development of technology brings a bunch of changes in every aspect in the world. In the education fields, it brings new concepts; a sense of easiness in learning and teaching process, such as, easiness of receiving information (knowledge) through internet, conducting teaching and learning process in distance area. This new concept is called shift – learning. E-learning systems are different from learning that is usually held in class (traditional learning). In industrial revolution 4.0, it is important that we use internet to fulfill the objective of education. This paper aims to identify the way fresh students from remote areas handle this situation. This research used descriptive qualitative. The research subjects consisted of 12 students of the English Language Study Program of Universitas Ahmad Dahlan in 2019. Data collection techniques were carried out using observation and interviews. From the student’s perspectives, it was found that Shift-learning (e – Learning) is not something new for them, Shift-learning (e – Learning) leads students to broaden their knowledge, making them flexible to access the materials. However, less supported facility becomes the significant challenge. It showed that most English students from remote areas are ready to use e-learning in learning English because e-learning is not something new to them. Although less supporting facility and guidance from lecturers become the challenges for students, these do not stop them from using e-learning.